Fungal mycelial mats used as textile by indigenous people of North America. (4th March 2021) - Blanchette, Robert A.; Haynes, Deborah Tear; Held, Benjamin W.; Niemann, Jonas; Wales, Nathan
ABSTRACT: The indigenous people of the United States and Canada long have used forest fungi for food, tinder, medicine, paint, and many other cultural uses. New information about historical uses of fungi continues to be discovered from museums as accessions of fungi and objects made from fungi collected over the last 150+ years are examined and identified. Two textiles thought to be made from fungal mats are located in the Hood Museum of Art, Dartmouth College, and the Oakland Museum of California. Scanning electron microscopy and DNA sequencing were used to attempt to identify the fungus that produced the mats. Although DNA sequencing failed to yield a taxonomic identification, microscopy and characteristics of the mycelial mats suggest that the mats were produced by Laricifomes officinalis . This first report of fungal mats used for textile by indigenous people of North America will help to alert museum curators and conservators as well as mycological researchers to their existence and hopefully lead to more items being discovered that have been made from fungal fabric.